PENINGKATAN KUALITAS LAPORAN KEUANGAN MENGGUNAKAN APLIKASI ZAHIR PADA USAHA DODI FARM DI KOTA PAYAKUMBUH - Rivandi, Muhammad; Andra, Yefrinal; Hidayat, Teguh; Wandi, Dedi (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The purpose of this community service activity (PkM) is to describe how to use the financial reporting application and implement the Zahir Accounting application in Dodi Farm. They held the activity on Saturday, Mei 31, 2025, Payakumbuh City The benefits of this activity are to help Dodi Farm to become successful MSME actors, increase productivity, orderly record every financial transaction through the Zahir Accounting application system so that they can obtain accurate information regarding financial position and performance, and dodi farm in developing its business. The forms of activities carried out are a form of training on the application of Zahir Accounting and mentoring programs regarding business activities and Zahir Accounting applications. With the application of the Zahir Accounting software, it will make it easier for the dodi to record transactions to improve the economy